1984
DOI: 10.1159/000176782
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase Activities in the Rat Intestinal Mucosa: Comparison between Standard Commercial and Semi-Synthetic Diets

Abstract: Two groups of rats were fed either a commercial (C group) or a semi-synthetic (S group) diet of very similar quantitative composition, which induce similar growth in the animals. Glycosyltransferase activities are very different in the two groups: fucosyltransferase is lower in S group than in C group, regardless of the expression of the results (specific activity versus protein or DNA). The other activities (galactosyl-, N-acetylglucosaminyl-, N-acetylgalactosaminyltransferases) are modified when expressed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This sug gests the sensitivity of the intestinal fucosylation process to variations in the animal diet. Our results on the chemical analysis of sialic acid and fucose-and lectin-binding characteristics of brush borders in suckling animals from the LP group are in agreement to the observations in adult animals [7], Al though, at present, no information is avail able on glycosyl-transferase activities of in testinal tissue in weanling rats subjected to nutritional stress, it is likely that the ob served changes in the fucosylation pattern of microvillus surface may be related to altera tions in fucosyl-transferase levels under these conditions. However, changes in the availability of substrates, fucosyl-substitution-reactive sites and various cofactors in volved in the fucosylation may also be impli cated in the observed aberrations of epithe lial cell surface glycosylation in response to maternal nutrition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This sug gests the sensitivity of the intestinal fucosylation process to variations in the animal diet. Our results on the chemical analysis of sialic acid and fucose-and lectin-binding characteristics of brush borders in suckling animals from the LP group are in agreement to the observations in adult animals [7], Al though, at present, no information is avail able on glycosyl-transferase activities of in testinal tissue in weanling rats subjected to nutritional stress, it is likely that the ob served changes in the fucosylation pattern of microvillus surface may be related to altera tions in fucosyl-transferase levels under these conditions. However, changes in the availability of substrates, fucosyl-substitution-reactive sites and various cofactors in volved in the fucosylation may also be impli cated in the observed aberrations of epithe lial cell surface glycosylation in response to maternal nutrition.…”
Section: Discussionsupporting
confidence: 91%
“…The membrane fucose levels and the binding of a-L-fucose-specific lectin, UEAi, were considerably more in pups from LP-diet-fed lactating rats. Interestingly, Biol et al [7] have shown that feeding a semisyn thetic diet to adult rats affects the fucosyltransferase levels without altering the sialyl-transferase activity in intestine. This sug gests the sensitivity of the intestinal fucosylation process to variations in the animal diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biol el al. [20] have reported stimulation of fucosyltransferase activity in intestine of adult rats fed semisynthetic diets.…”
Section: Discussionmentioning
confidence: 99%